The Dead Sea scrolls and the study of the humanities method, theory, meaning : proceedings of the Eighth Meeting of the International Organization for Qumran Studies (Munich, 4-7 August, 2013) - Hartog, Pieter B.; Schofield, Alison.; Thomas, Samuel I. (Studies on the Texts of the Desert of Judah, 2018)
The Dead Sea Scrolls and the Study of the Humanities explores the use of methods, theories, and approaches from the humanities in the study of the Dead Sea Scrolls. The volume contains ten essays on topics ranging from New Philology and socio-linguistics to post-colonial thinking and theories of myth.